Call of God, The : Women Doing Theology in Peru - Powers, Tom, S.J (Book collections on Project MUSE., 2003)
"Based on conversations with women in one of the poorest neighborhoods in Lima, Peru, The Call of God explores how their faith provides them with an understanding amidst extreme poverty, violence, and displacement. Peru was the birthplace of liberation theology and the poor women of that country were instrumental in its original elucidation."--Jacket.